Seasonal variation of plankton population of Borobila beel in Rangpur district (University Journal of Zoology, Rajshahi University, 2008)
Seasonal variation of the plankton populations with some water quality parameters of Borobila beel, Rangpur district was carried out during July 2003 to June 2004. Total plankton ranged from 98.3×104 to 35.0×105 cells/l with mean values of 19.67±9.77×105 cells/l. A total of 51 genera of planktons were recorded belonging to Chlorophyceae, Bacillariophyceae, Cyanophyceae, Euglenophyceae, Dinophyceae, Crustacea and Rotifera. Among the phytoplankton, Euglenophyceae was the most dominant group and contributing 33% of total phytoplankton in Borobila beel. The greatest abundance of phytoplankton was recorded in November with an average number 28.83×105 cells/l. The minimum abundance of phytoplankton was recorded in January (61.7×104 cells/l). Among the zooplanktons Crustacea was dominant, contributing 71% of the total zooplankton population. The abundance of zooplankton showed two peaks of which one in the month of August (81.7x 104 cells/l) and another in the month of May (16.7 x104 cells/l). Phytoplankton and zooplankton have a nominal positive relationship. Zooplankton was less increased with the increasing of phytoplankton. Key words: Water quality parameters, plankton population, Borobila beel. Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 49-54